Reconnection in the Martian Magnetotail: Hall‐MHD With Embedded Particle‐in‐Cell Simulations. Issue 5 (18th May 2018) - Ma, Yingjuan; Russell, Christopher T.; Toth, Gabor; Chen, Yuxi; Nagy, Andrew F.; Harada, Yuki; McFadden, James; Halekas, Jasper S.; Lillis, Rob; Connerney, John E. P.; Espley, Jared; DiBraccio, Gina A.; et al.
Abstract: Mars Atmosphere and Volatile EvolutioN (MAVEN) mission observations show clear evidence of the occurrence of the magnetic reconnection process in the Martian plasma tail. In this study, we use sophisticated numerical models to help us understand the effects of magnetic reconnection in the plasma tail. The numerical models used in this study are (a) a multispecies global Hall‐magnetohydrodynamic (HMHD) model and (b) a global HMHD model two‐way coupled to an embedded fully kinetic particle‐in‐cell code. Comparison with MAVEN observations clearly shows that the general interaction pattern is well reproduced by the global HMHD model. The coupled model takes advantage of both the efficiency of the MHD model and the ability to incorporate kinetic processes of the particle‐in‐cell model, making it feasible to conduct kinetic simulations for Mars under realistic solar wind conditions for the first time. Results from the coupled model show that the Martian magnetotail is highly dynamic due to magnetic reconnection, and the resulting Mars‐ward plasma flow velocities are significantly higher for the lighter ion fluid, which are quantitatively consistent with MAVEN observations. The HMHD with Embedded Particle‐in‐Cell model predicts that the ion loss rates are more variable but with similar mean values as compared with HMHD model results. Key Points: Model results show that the Martian magnetotail is highly dynamic due to magnetic reconnection The numerical simulations predict that the Mars‐ward plasma flow, due to magnetic reconnection, is faster for lighter ions, consistent with MAVEN observations The HMHD EPIC model simulations predict that the ion loss rates are more variable but with similar mean values as compared with HMHD model